Evaluating the Potential Benefit of a Combined Weight Loss Program in Dogs and Their Owners - Niese, J. Rebecca; Mepham, Tierney; Nielen, Mirjam; Monninkhof, Evelyn M.; Kroese, Floor M.; de Ridder, Denise T. D.; Corbee, Ronald J. (Frontiers in Veterinary Science, 2021)
Introduction: Little has been published on the psychological bond between the owner and the pet, and how this might influence shared habits that could lead to overweight and obesity. If the owner would see the dog as a weight loss partner and therefore this could increase the motivation to follow the assigned diet and exercise guidelines. Objective: The aim of this research was to evaluate the potential mutual effects of weight loss programs for both dogs and dog owners. Methods: Two studies were conducted: In the human-centered trial, 60 dog owners were enrolled, who signed up to receive dietary and exercise recommendations to lose weight themselves during an eight week period, from which 29 were randomly assigned to also get recommendations for their dog. For the dog-centered trial, we selected 13 dog owners that wanted their dog to lose weight during a six week period, from which 7 were randomly assigned to also get recommendations for themselves. A questionnaire was used to evaluate diet and exercise habits, as well as information about the relationship between the dog and owner. Results: The average weight loss was 2.6% in the owner+dog group (n=29) and 2.3% in the owner only group (n=31) (p>0.05). The overweight dogs in the owner+dog group (n=12) lost 3.7% of their body weight, compared to 1.2% in the overweight dogs from the owner only group (n=12) (p>0.05). In the dog-centered trial, the 7 dogs in the dog+owner group lost 8.0% of their body weight, versus 8.3% in the 6 dogs in the dog only group (p>0.05). The owners in the dog+owner group lost 2.5% of their body weight, compared to 0.5% in the dog only group (p>0.05). In both trials owners’ perceived responsibility for both their own and their dogs’ weight significantly increased, habit strength regarding unhealthy feeding and exercise behaviors in relation to the dogs decreased, and self-efficacy in relation to providing the dog with healthy food and exercise increased. Conclusion: These findings support mutual benefits of weight loss programs for dogs and dog owners, and support future weight loss programs to be a One Health approach.